An optical water velocity sensor for open channel flows - Dvorak, Joseph Scot (Kansas State University, 2012)
An optical sensor for determining water velocity in natural open channels like creeks and rivers has been designed and tested. The sensor consists of a plastic body which is shaped so that water flows through a U-shaped channel into which are mounted LEDs and matching phototransistors at various angles. A small amount of dye is injected into the water just upstream of two sets of LEDs and phototransistors which are spaced 4 cm apart. The time delay between the dye’s effects on these signals depends on water velocity and is determined using a biased cross correlation calculation. In addition to providing velocity, the LEDs and phototransistors can also be used to estimate soil sediment concentration. A previous version of the sensor was tested in enclosed flow to confirm that the general design of the sensor, including LEDs, phototransistors, dye and electronics, would indeed work to detect the velocity of water flowing through the sensor. Although the conditions for the test were unlike those experienced in natural open channels, the ability to catch all the fluid flowing through the sensor provided a simple confirmation of the velocity estimate that was not available in field settings. Further testing in the field then confirmed that the sensor worked in the field but also identified several areas needing improvement. Computational fluid dynamics was used to improve the sensor body. The electronics and program running the sensor were also redesigned. After making these improvements, a new version of the sensor was produced. The testing of the new version of the sensor confirmed its ability to accurately detect velocity in natural open channels. The velocity measurements from this sensor were compared to the commercially available Flowtracker velocity sensor. A regression analysis on the measurements from the two sensors found that the velocity measurements from each sensor were nearly identical across a range of velocities. Other tests established that the electronics and programming running the sensor performed as designed. The development and testing of this sensor has resulted in a system which works in natural open channels like creeks and rivers.
Keywords: Flow velocity measurement; Optical sensor; Cross correlation; Natural open channel; Computational fluid dynamics; Engineering, Agricultural (0539)